Expression and immunogenicity of HBV surface antigens following in vitro and in vivo gene delivery using recombinant adenoviruses - Neves, Keila Dias (University of the Witwatersrand, Johannesburg, 2024)
Hepatitis B virus (HBV) infection poses a global health problem affecting almost 300 million people. Immunisation remains one of the most effective methods of HBV prevention. The HBV surface antigen (HBsAg) is one of the primary clinical markers for acute or chronic HBV infection. It is an important component of anti-HBV vaccines because of its presence on the viral envelope and interaction with neutralising antibodies (NAbs). Current vaccines against HBV, which deliver only the HBV small surface antigen (SHBsAg) as a purified peptide in a 3-dose regimen, are often less effective in people over the age of 40 years and in immuno compromised individuals. Additionally, these vaccines are limited to mostly humoral immunity. Recent widespread use of viruses as vectors for vaccine delivery has propelled use of adenoviruses (Ads) to the front line of vaccine research. Adenoviral vectors (AdVs) are attractive candidates for anti-HBV vaccine design because of their ability to induce both cell- mediated and humoral immune responses. Therefore, this study was conducted to assess the efficiency of AdVs in the delivery of HBV SHBsAg or large surface antigen (LHBsAg) and induction of HBV specific immune responses. Recombinant AdVs encoding either the LHBsAg (Ad5-LHBsAg), SHBsAg (Ad5-SHBsAg) or Firefly luciferase (FLuc) reporter (Ad5-FLuc) were produced. Infection of Human Embryonic Kidney 293T (HEK293T) cells with Ad5-SHBsAg showed dose-dependent expression of SHBsAg in both supernatant and lysate samples. However, as expected, significantly higher expression of LHBsAg was seen in lysates from cells infected with Ad5-LHBsAg when compared to supernatant samples, because the LHBsAg peptide is not naturally secreted. Intramuscular injection of Ad5-FLuc to Balb/c mice showed significant expression of FLuc at days 1 and 3 after injection with Ad5-FLuc, with expression decreasing by day 7, as expected. Analysis of cellular immunity showed HBV- specific IFN-γ responses in mice vaccinated with Ad5-SHBsAg, Ad5-LHBsAg and EUVAX-B control. Additionally, anti-HBsAg antibodies were detected in mice vaccinated with Ad5- SHBsAg and EUVAX-B. This study shows that AdVs are promising candidates for novel anti- HBV vaccine design and may circumvent current challenges of available anti-HBV vaccines by inducing more robust immune responses while decreasing the doses required for immunisation. This research bodes well for future work in the development of vaccine regimens involving other AdVs against a variety of infectious diseases
A dissertation submitted in engulfment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, Johannesburg, 2024
Keywords: HBV; Vaccines; Adenoviruses; UCTD; SDG-3: Good health and well-being